The Use of Biomass in the Visegrad Group Countries and Its Determinants - Piotr Kułyk; Mariola Michałowska (Energies, 2025)
This article aims to assess the conditions and prospects for biomass utilization in the Visegrad Group (V4) countries. Additionally, the relationship between biomass energy production and greenhouse gas emissions was examined. A key component of the analysis involved identifying potential directions for the development of biomass utilization in the pursuit of the sustainable development of agricultural enterprises. In relation to these research objectives, a hypothesis was formulated regarding the causal relationship between biomass energy consumption and economic growth, the abundance of natural resources, and income in reference to the European Union economies. Both static and dynamic panel studies were applied. The conducted research revealed the complex nature of the conditions influencing biomass utilization. The study period covered the years 2004–2022. A negative correlation was found between the use of biomass and greenhouse gas emissions. At the same time, factors favoring biomass utilization included economic growth, the level of natural resource consumption per capita, and government policies aimed at increasing the share of renewable resources in the economy.